2023
DOI: 10.1007/s00442-023-05379-w
|View full text |Cite
|
Sign up to set email alerts
|

Egg components and offspring survival vary with group size and laying order in a cooperative breeder

Abstract: Prenatal resource allocation to offspring can be influenced by maternal environment and offspring value, and affect offspring survival. An important pathway for flexible maternal allocation is via egg components such as nutrients and hormones. In cooperative breeders, females with helpers may increase resource allocation to eggs—‘differential allocation’—or reduce it—‘load-lightening’. Yet, helper effects on egg composition have been poorly studied. Moreover, it is unknown how helpers’ presence modulates layin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 96 publications
1
6
0
Order By: Relevance
“…Instead, we found that the predator treatment similarly affected females regardless of their group size, which suggests that females with more helpers may not be at an advantage particularly under high predation risk environments. This corroborates previous results in this species suggesting lack of helper effects on egg mass and clutch size, either in general or in interaction with climatic conditions and nest predation risk ( Fortuna et al 2021 ; but see helper effects on egg content in Fortuna et al 2023 ). In sociable weavers, it has never been investigated whether predation risk decreases in larger breeding groups, and this would help clarify whether group size confers protection or other advantages to individuals before and during rearing ( Sorato et al 2012 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Instead, we found that the predator treatment similarly affected females regardless of their group size, which suggests that females with more helpers may not be at an advantage particularly under high predation risk environments. This corroborates previous results in this species suggesting lack of helper effects on egg mass and clutch size, either in general or in interaction with climatic conditions and nest predation risk ( Fortuna et al 2021 ; but see helper effects on egg content in Fortuna et al 2023 ). In sociable weavers, it has never been investigated whether predation risk decreases in larger breeding groups, and this would help clarify whether group size confers protection or other advantages to individuals before and during rearing ( Sorato et al 2012 ).…”
Section: Discussionsupporting
confidence: 92%
“…Hence, we cannot determine whether this adjustment was similar for the remaining eggs or exclusive to later-laid ones, and previous investigations in this population suggest only ca. 20–25% repeatability in yolk mass within clutches ( Fortuna et al 2023 ). Nevertheless, a decrease in yolk mass—generally or specifically in later-laid eggs—might represent a reduced female investment in reproduction, which may lead to brood reduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While we cannot formally assess the relative importance for offspring fitness of this potentially "indirect" helper effect on maternal pre-natal investment and the direct causal positive effect of helpers on post-natal provisioning (demonstrated in [35]), the direct post-natal helper effect may still dominate, as the within-mother effect of female helper number on egg volume is modest compared to the within-mother effect of female helper number on the overall rates of post-natal provisioning (Fig 1 in [35]). That said, the effect size for the change in egg volume could underestimate the fitness consequences for offspring of the maternal pre-natal response to helpers, as any accompanying helper-induced changes in egg composition [7,40] could yield fitness effects that differ in magnitude from the observed change in egg volume. Second, while helper-induced reductions in maternal post-natal workloads are typically thought to benefit mothers (e.g., by improving maternal survival; [5,7]), our findings highlight that associated changes in egg investment could pass these benefits, in part or whole, to the offspring being reared.…”
Section: Plos Biologymentioning
confidence: 99%
“…We also confirm that our findings are not complicated by parallel maternal plasticity in clutch size according to helper numbers, by verifying that within-mother variation in female and male helper numbers does not predict clutch size. As egg traits often vary across the laying sequence [38,39] and associations between helper numbers and egg composition have also been found to vary across the laying sequence [40], our analysis of egg volume also controls for effects of egg position within the laying sequence and allows for interactive effects of helper numbers and egg position. We then investigate whether within-mother variation in female and male helper numbers predict variation in the mother's nestling feeding rate (again utilizing a large longitudinal data set; 124 broods being fed by 50 mothers in 34 social groups; 1 to 7 broods [median = 2] per mother).…”
Section: Introductionmentioning
confidence: 99%